2021
DOI: 10.1021/acscatal.1c02609
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Sensitized Photoelectrosynthesis Cells for Benzyl Alcohol Oxidation Using a Zinc Porphyrin Sensitizer and TEMPO Catalyst

Abstract: based DSPEC using a zinc porphyrin (ZnP) sensitizer and a TEMPO organo-catalyst that quite efficiently catalyzes light driven oxidation of methoxybenzyl alcohol into aldehyde. Two dyads ZnP-TEMPO, differing by the anchoring group (carboxylic acid and hydroxamic acid) on ZnP, were prepared and their electrochemical, absorption, emission properties were recorded and quantum chemical modelling was realized. The photovoltaic performances in DSSCs were first examined in order to optimize the dyeing conditions and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 87 publications
1
41
0
Order By: Relevance
“…More interestingly, the hybrid system turns out to be effective in the photo-oxidation of natural lignin in the acetone solution, with measured J of ∼130 μA/cm 2 under comparable experimental conditions. Odobel et al reported the synthesis of a molecular triad based on a ruthenium tris (bipyridine) complex as the photosensitizer, connected on one side to the TEMPO alcohol oxidation catalyst and on the other side to a naphthalenedicarboxyanhydride dicarboximide (NDADI) electron acceptor ( Figure 1H ) ( Nikoloudakis et al, 2021 ). When attached onto nano- ITO, the triad effectively mediates the oxidation of para -methoxybenzyl alcohol in a pH 10 carbonate buffer solution on visible light irradiation at a bias of +0.4 V versus SCE.…”
Section: Systems Based On Ruthenium Complexesmentioning
confidence: 99%
See 3 more Smart Citations
“…More interestingly, the hybrid system turns out to be effective in the photo-oxidation of natural lignin in the acetone solution, with measured J of ∼130 μA/cm 2 under comparable experimental conditions. Odobel et al reported the synthesis of a molecular triad based on a ruthenium tris (bipyridine) complex as the photosensitizer, connected on one side to the TEMPO alcohol oxidation catalyst and on the other side to a naphthalenedicarboxyanhydride dicarboximide (NDADI) electron acceptor ( Figure 1H ) ( Nikoloudakis et al, 2021 ). When attached onto nano- ITO, the triad effectively mediates the oxidation of para -methoxybenzyl alcohol in a pH 10 carbonate buffer solution on visible light irradiation at a bias of +0.4 V versus SCE.…”
Section: Systems Based On Ruthenium Complexesmentioning
confidence: 99%
“…The lower oxidation power required for the transformation of organics can open new opportunities for a plethora of porphyrin dyes which usually require ring functionalization to achieve potentials suitable for water oxidation. Within this framework, one elegant system was recently proposed by Odobel et al, combining a zinc porphyrin and a TEMPO catalyst onto a TiO 2 semiconductor ( Figure 2A ) ( Nikoloudakis et al, 2021 ). The system was successfully applied in the photoelectrochemical oxidation of benzyl alcohol derivatives in the presence of methyl imidazole as the base, with better performances observed in aqueous borate buffer with respect to the acetonitrile solution.…”
Section: Systems Based On Noble-metal–free and Organic Sensitizersmentioning
confidence: 99%
See 2 more Smart Citations
“…Volatile organic compounds (VOCs) are generated and released extensively from modern industries such as petroleum refining, chemical raw material production, and electronic equipment manufacturing. Xylene isomers ( m -, p -, and o -xylene), as a class of typical aromatic VOCs, are particularly hazardous in causing severe diseases and endangering the ecological environment. As one of the indispensable technology for air purification, the massive application of photocatalysis in the decomposition of VOCs confirms its great potential. However, the rapid deactivation is almost inevitable against the accumulation of ring-containing intermediates on the photocatalyst surface during VOC decomposition reactions. It is definite that the ring-opening reaction is considered to be the rate-determining step for the complete decomposition of aromatic VOCs pollutants. Thus, the subtle mechanism of the ring-opening reaction requires a comprehensive investigation for the development of deactivation-resistant photocatalysts.…”
Section: Introductionmentioning
confidence: 99%